Implementation of Legislation Related to Construction Waste among Contractors - Koh, Chloe; Seow, Ta Wee; Omar, Roshartini; Sarpin, Norliana (Research in Management of Technology and Business, 2023)
The fast improvement in Malaysia has expanded the interest of construction material usage for development purposes and then again, the substantial waste was likewise expanding consistently, and it has been brought up as the most produced waste from development industry. When dealing with construction waste which involves in any party for assuring construction site were most probably lack of regulations and irresponsibility of local authorities to manage the issue well. Level of awareness on the legislation towards environmental in the field of contractors were lower among project developers with regards of laws and regulations stated within the implementation in Malaysia. This study aims to identify the perception of contractors and to investigate the implementation of legislation related to construction waste among contractors. Besides, this research identified different types of construction waste in construction site and investigated the construction waste generated on how implementation of laws and regulations helped increase the awareness. The questionnaires have been distributed to G7 construction practitioners such as consultants, contractors, site supervisor, engineers, and project managers in Johor Bahru. Thus, the survey was obtained from 60 respondents and were analyzed using Statistical Package for Social Science (SPSS) system in determining the mean score values. In conclusion, this research had improved the economical and overall construction industry quality where the acknowledgment of legislation in the study area provided a clearer view in enhancing a better atmosphere.